Potential of Pineapple Peel (Ananas Comosus) as a Toothpaste Base Material for Mouth Refreshing - Nisaul Khairati; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Almost 90% of Indonesians have cavities, swollen gums and abscesses, which is due to the fact that most Indonesians have their teeth flattened in the wrong way, while this will affect dental health. The purpose of this research is to study the potential of pineapple peel (ananas SUS) for the basic composition of toothpaste to refresh the mouth. This research method is experimental research. Research on experiments is research that is held to determine the consequences of something that is done intentionally by researchers. In the organoleptic assessment of toothpaste color, taste, texture, and aroma are in accordance with the standard sni 8861: 2020. Data collection techniques and equipment with organic assessments will be presented in the appendix. Analysis of toothpaste is the color of toothpaste which has a percentage of ss = 40% and s = 0% as ifts = 60%. Aroma on toothpaste which has a percentage as ss = 100%, s =0% and ts =0%. Texture on toothpaste which has a percentage as ss = 80% and s = 0% while ts = 20%. The toothpaste has a percentage of ss = 86.67% and s = 0% while ts = 1333%. Pineapple peel toothpaste is a toothpaste. The ingredients of this toothpaste include pineapple peel, salt, charcoal, mint leaves and green tea. This toothpaste is great for people whose teeth are sensitive, but for people whose teeth are normal, the toothpaste can also be used because the toothpaste is natural.